Caenorhabditis evolution in the wild. (30th June 2015) - Cutter, Asher D.
<x xml:space="preserve">Abstract</x> Recent research has filled many gaps about Caenorhabditis natural history, simultaneously exposing how much remains to be discovered. This awareness now provides means of connecting ecological and evolutionary theory with diverse biological patterns within and among species in terms of adaptation, sexual selection, breeding systems, speciation, and other phenomena. Moreover, the heralded laboratory tractability of C. elegans, and Caenorhabditis species generally, provides a powerful case study for experimental hypothesis testing about evolutionary and ecological processes to levels of detail unparalleled by most study systems. Here, I synthesize pertinent theory with what we know and suspect about Caenorhabditis natural history for salient features of biodiversity, phenotypes, population dynamics, and interactions within and between species. I identify topics of pressing concern to advance Caenorhabditis biology and to study general evolutionary processes, including the key opportunities to tackle problems in dispersal dynamics, competition, and the dimensionality of niche space.